Invertebrados como bioindicadores de perturbación en la Reserva de Biosfera del Manu - Amaru Castelo, Javier (2024)
Introduction: Bioindicator monitoring is a crucial conservation strategy within natural protected areas. Various taxonomic groups have been investigated as bioindicators due to their distinctive attributes, including ease of sampling, differential responses to disturbances, associations with species richness, and accessible taxonomy. Objective: To compare the potential of four taxa (Chilopoda, Scarabaeidae, Carabidae, and Pompilidae) as environmental bioindicators, considering their ease of collection, presence of changes in community composition due to disturbances, including species with preferences for disturbed or conserved areas; and to correlate their diversity with the diversity of other taxa. Methods: The study was conducted at the Manu Learning Centre Biological Station in the Manu Biosphere Reserve, which comprises three areas along a disturbance gradient. Specimens were collected using pitfall traps, yellow pan traps, Malaise traps, and monoliths from May to June in 2021. Ease of collection was measured in terms of richness and abundance; changes in the community composition were assessed using similarity analysis, non-metric multidimensional scaling, and beta diversity partitioning; presence of species with preferences was analyzed using correspondence analysis and G. Williams’ goodness-of-fir test; and diversity correlation using the Spearman index. Results: Among the taxa investigated, Scarabaeidae and Pompilidae were the easiest to collect. Changes in composition were observed in all taxa but were significant only in Chilopoda and Scarabaeidae. All taxa exhibited species with preferences for disturbed and undisturbed environments. There was a high correlation in diversities among Carabidae, Scarabaeidae, and Chilopoda. Conclusions: Our findings underscore the diverse responses exhibited by taxa along a disturbance gradient. Notably, Scarabaeidae and Chilopoda emerged as particularly robust bioindicators within the studied ecosystem.